Lexibank, a public repository of standardized wordlists with computed phonological and lexical features - Johann-Mattis List; Robert Forkel; Simon J. Greenhill; Christoph Rzymski; Johannes Englisch; Russell D. Gray (Scientific Data, 2022)
Measurement(s) expressions Technology Type(s) data aggregation Factor Type(s) none Sample Characteristic - Organism human language Sample Characteristic - Location global scale